2005
DOI: 10.1021/es0500815
|View full text |Cite
|
Sign up to set email alerts
|

Macro- and Nanoscale Observations of Adhesive Behavior for Several E. coli Strains (O157:H7 and Environmental Isolates) on Mineral Surfaces

Abstract: Subsurface biobarriers can be conceived to attenuate the migration of pathogens by adhesion to mineral surfaces. Candidate biobarrier materials of varied surface characteristics (dolomite, alpha-alumina, silica, pyrophyllite, and Pyrax (a composite form of pyrophyllite, mica, and silica)) were tested for Escherichia coli adhesive capacity in macroscale continuous-flow columns. Atomic force microscopy (AFM) was used to determine nanoscale interaction energies. Predicted attractive interaction energies correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
73
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 76 publications
11
73
1
Order By: Relevance
“…The low sticking efficiency values obtained in this work express the importance of the use of sufficiently long columns in bacterial transport studies, as the possibility of obtaining these values is not possible with short columns. Note that most values measured in laboratory setups reported in the literature range between 0.02 to 0.9 (Foppen and Schijven, 2006), and in some cases values greater than 1 were measured (Lutterodt et al, 2009a,b, Paramanova et al, 2006, Morrow et al, 2005, Shellenberger et al, 2002. These values are 2 to 5 orders of magnitude higher than results obtained in this work.…”
Section: Low Sticking Efficiencies Inter-strain and Intra-strain Hetcontrasting
confidence: 41%
See 4 more Smart Citations
“…The low sticking efficiency values obtained in this work express the importance of the use of sufficiently long columns in bacterial transport studies, as the possibility of obtaining these values is not possible with short columns. Note that most values measured in laboratory setups reported in the literature range between 0.02 to 0.9 (Foppen and Schijven, 2006), and in some cases values greater than 1 were measured (Lutterodt et al, 2009a,b, Paramanova et al, 2006, Morrow et al, 2005, Shellenberger et al, 2002. These values are 2 to 5 orders of magnitude higher than results obtained in this work.…”
Section: Low Sticking Efficiencies Inter-strain and Intra-strain Hetcontrasting
confidence: 41%
“…The Ag43 adhesin is known to establish autoaggregation of cells through Ag43-Ag43 interactions by a kind of intercellular handshake mechanism (Klemm et al, 2004;Hasman et al, 2000) resulting in the retardation of cell movement (Yang, 2005). In our case, such mechanism might have played a role, but, more importantly, we found that Ag43 also played a crucial role in the initial attachment of bacteria cells to the quartz grain surfaces.…”
Section: Ag43 Expression and Motilitymentioning
confidence: 45%
See 3 more Smart Citations